Disrupting the Patrón Indigenous Land Rights and the Fight for Environmental Justice in Paraguay's Chaco - Correia, Joel (University of California Press, 2023)
In Paraguay's Chaco region, cattle ranching drives some of the world's fastest deforestation and most extreme inequality in land tenure, with grave impacts on Indigenous well-being. Disrupting the Patrón traces Enxet and Sanapaná struggles to reclaim their ancestral lands from the cattle ranches where they labored as peons-a decades-long resistance that led to the Inter-American Court of Human Rights and back to the frontlines of Paraguay's ranching frontier. The Indigenous communities at the heart of this story employ a dialectics of disruption by working with and against the law to unsettle enduring racial geographies and rebuild territorial relations, albeit with uncertain outcomes. Joel E. Correia shows that Enxet and Sanapaná peoples enact environmental justice otherwise: moving beyond juridical solutions to harm by maintaining collective lifeways and resistance amid radical social-ecological change. Correia's ethnography advances debates about environmental racism, ethics of engaged research, and Indigenous resurgence on Latin America's settler frontiers. "A crucial and incisive contribution to our understanding of racialized geographies, settler capitalism, and environmental and Indigenous justice." - Gastón R. Gordillo, author of Rubble: The Afterlife of Destruction "Focusing on the racial and cultural implications of land and labor in Indigenous struggles in Paraguay, Correia expands our focus on environmental concerns to include human rights, cultural rights, and the need for legal and political justice." - Nancy Postero, author of The Indigenous State: Race, Politics, and Performance in Plurinational Bolivia "A story of the underrepresented peoples of Paraguay, their endurance under multiple cycles of dispossession, and the various forms that their resistance takes." - Gabriela Valdivia, coauthor of Oil, Revolution, and Indigenous Citizenship in Ecuadorian Amazonia